Primary vs nodal site PET/CT response as a prognostic marker in oropharyngeal squamous cell carcinoma treated with intensity‐modulated radiation therapy. Issue 9 (11th May 2020) - Eckstein, Jacob Matthew; Nolan, Nicole; Healy, Erin; Wright, Chadwick Lewis; Jain, Angita; Barney, Christian Louis; Washington, Iman; McElroy, Joseph Paul; Grecula, John Christopher; Wobb, Jessica Lynn; Mitchell, Darrion Luther; Miller, Eric; et al.
Abstract: Background: Positron emission tomography/computed tomography (PET/CT) in staging of advanced oropharyngeal squamous cell carcinoma (OPSCC) and at 3 months posttreatment (PETpost) is often utilized to assess response. The significance of lymph node vs primary site treatment response is incompletely understood. Methods: We reviewed 230 patients treated with radiation therapy. PETpost response was graded at primary and nodal sites and correlated with survival. Results: Median age was 58, and 83% were p16‐positive. Median follow‐up was 24.3 months. Nodal response at PETpost predicted improved 2‐year local recurrence‐free survival (LRFS) (93% vs 72%, P  =.004), 2‐year disease‐free survival (DFS) (80% vs 61.3%, P  =.021), and 2‐year overall survival (OS) (89% vs 83%, P  =.051), while primary response only predicted improved 2‐year LRFS (91% vs 76% P = .035). Conclusion: In OPSCC patients, both nodal and primary response at 3 months on PET/CT predicted for improved LRFS, but only nodal response predicted DFS and OS.